Safety, tolerability, and pharmacokinetics of a novel anti-influenza agent ZX-7101A tablets in healthy chinese participants: A first-in-human phase I clinical study - Wu, Junzhen; Wei, Qiong; Jin, Yi; Cao, Guoying; Yu, Jicheng; Wu, Xiaojie; Yang, Xinyi; Li, Yilin; Liu, Mei; Qin, Xiaoli; Ai, Jingwen; Wang, Yin; et al. (International journal of antimicrobial agents, 2025)
•ZX-7101A is a novel cap-dependent endonuclease inhibitor.•A single dose of 40–320 mg ZX-7101A was safe and well-tolerated in healthy subjects.•A single oral dose of 40 mg and 80 mg was expected to exhibit adequate in vivo anti-influenza activity.•A high-fat meal decreased the exposure level of ZX-7101, while C24 still exceeded the pharmacodynamic target values of ZX-7101.•A single oral dose of 40 and 80 mg is proposed for use in phase II/III clinical trials. We investigated the safety, tolerability, and pharmacokinetics of ZX-7101A tablets, a novel cap-dependent endonuclease inhibitor, in healthy participants in a first-in-human study. The single ascending dose (SAD) part of the study included 40, 80, 160, 240, and 320 mg dose cohorts with10 participants in each dose cohort (8 participants received ZX-7101A tablets and 2 participants received placebo). The food effect (FE) part of the study was a randomised, 2-cycle, 2-way crossover design, which enrolled 16 participants to receive a single oral dose of 80 mg ZX-7101A tablets. ZX-7101A tablets were safe and well-tolerated in both SAD and FE studies. No participant died or experienced SAE, or withdrew prematurely. The prodrug ZX-7101A was rapidly transformed into the active ingredient ZX-7101 after a single oral dose of 40–320 mg. The blood concentration of ZX-7101A was below the lower limit of quantification at most time points. ZX-7101 reached peak concentration about 3–4 h postdose in all dose cohorts. The elimination half-life of ZX-7101 was 83.01–125.55 h, and AUC0-24 was 1655.4–11483.7 h*ng/mL. The FE part showed that the high-fat meal significantly affected the exposure parameters compared to the fasted condition. The Cmax and AUC0-t of ZX-7101 under the fasted condition were 1.73 and 1.78 times those under the fed condition, respectively. A single oral dose of 40 mg and 80 mg ZX-7101A tablets achieved sufficient ZX-7101 exposure for effectively inhibiting influenza A and B viruses and avian influenza viruses. These findings support 40 mg and 80 mg of ZX-7101A tablets as single dose regimens for use in phase II/III clinical trials. This study was registered at chinadrugtrials.org.cn (identifier: CTR20212778). [Display omitted]